Establishment of 3D-printed Child Manikins Using Anthropometric Data of 6- and 10-year-old ASEAN Children - Ahmad Tajudin, M.H.; Abu Husain, N.; Che Husin, S.M.; Mohd Zaki, N.I.; Abu Husain, M.K.; Adanan, A.F.; Zulkifli, M.A.R.; Ma’aram, A.; Sarip, R.; Ahmad, Y.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
The New Car Assessment Programme for Southeast Asian Countries (ASEAN NCAP) has been working hard to increase vehicle safety levels in the ASEAN region. To ensure a significant impact on the ASEAN community, few enhancements need to be made to their test methodology and facilities. As an example, ASEAN NCAP is using child manikins with generic build in their vehicle safety assessment. Meanwhile, vehicle manufacturers and product developers are also using these generic references in their product designs such as the seat restraint system, child seat design, etc. For the improvement of vehicle safety especially for the ASEAN region, dedicated manikins with ASEAN anthropometric measurements are necessary. This paper aims to describe the development of 3D-printed manikins based on anthropometric data of ASEAN children aged 6 and 10 years old. The completed prototypes will be tested using a selected vehicle safety assessment (i.e., Child Restraint System installation) and intended to be applied for design refinement of vehicle safety systems.